2014
DOI: 10.3810/pgm.2014.07.2781
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole Treatment of Frequent Heartburn: Two Randomized, Double-Blind, Placebo-Controlled Trials

Abstract: A 14-day regimen of esomeprazole 20 mg once daily was effective for treating frequent heartburn in subjects who are likely to self-treat with over-the-counter medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…16 The current findings are consistent with those from 2 recently published clinical studies of esomeprazole 20 mg given over 2 weeks in subjects with frequent heartburn who were likely to use an OTC PPI. 18 Likewise, these data are consistent with those from 2-week studies of other OTC PPIs, including omeprazole and lansoprazole, available in some countries. Those studies demonstrated the efficacy of OTC PPI treatment using many of the end points included in the present analyses.…”
Section: Discussionsupporting
confidence: 81%
“…16 The current findings are consistent with those from 2 recently published clinical studies of esomeprazole 20 mg given over 2 weeks in subjects with frequent heartburn who were likely to use an OTC PPI. 18 Likewise, these data are consistent with those from 2-week studies of other OTC PPIs, including omeprazole and lansoprazole, available in some countries. Those studies demonstrated the efficacy of OTC PPI treatment using many of the end points included in the present analyses.…”
Section: Discussionsupporting
confidence: 81%
“…[8] Similar results were seen for heartburn-free days and nights. These effects were observed with esomeprazole 20 mg as early as the first four days of treatment, with significantly more subjects experiencing heartburn-free 24-hour days during this period (P = 0.0053 and P < 0.0001 vs. placebo in Study 1 and Study 2, respectively).…”
Section: Introductionsupporting
confidence: 84%
“…The conduct of these studies has been published in detail previously [8] and is summarized here briefly. Both studies were conducted in accordance with the ethical principles that have their origin in the Declaration of Helsinki and are consistent with International Council for Harmonisation and Good Clinical Practice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations